2013
DOI: 10.1093/nar/gkt1091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between protein Snu13p/15.5K and the Rsa1p/NUFIP factor and demonstration of its functional importance for snoRNP assembly

Abstract: The yeast Snu13p protein and its 15.5K human homolog both bind U4 snRNA and box C/D snoRNAs. They also bind the Rsa1p/NUFIP assembly factor, proposed to scaffold immature snoRNPs and to recruit the Hsp90-R2TP chaperone complex. However, the nature of the Snu13p/15.5K–Rsa1p/NUFIP interaction and its exact role in snoRNP assembly remained to be elucidated. By using biophysical, molecular and imaging approaches, here, we identify residues needed for Snu13p/15.5K–Rsa1p/NUFIP interaction. By NMR structure determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 69 publications
10
67
1
Order By: Relevance
“…GST pull down and Y2H experiments previously revealed a possible interaction between Rsa1p and Pih1p (21), and accordingly, we found that Rsa1p is required to tether Pih1p−Tah1p to a [C/D RNA−Snu13p] complex (29). Nop58p was initially shown to interact with Pih1p (31), and previous Y2H assays (21) and the present in vitro binding assays (Figure 1H) have revealed that Nop58p also associates with the purified Rsa1p 230−375 –Hit1p and Snu13p–Rsa1p 230−375 –Hit1p complexes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…GST pull down and Y2H experiments previously revealed a possible interaction between Rsa1p and Pih1p (21), and accordingly, we found that Rsa1p is required to tether Pih1p−Tah1p to a [C/D RNA−Snu13p] complex (29). Nop58p was initially shown to interact with Pih1p (31), and previous Y2H assays (21) and the present in vitro binding assays (Figure 1H) have revealed that Nop58p also associates with the purified Rsa1p 230−375 –Hit1p and Snu13p–Rsa1p 230−375 –Hit1p complexes.…”
Section: Discussionsupporting
confidence: 56%
“…First, as Snu13p is known to interact with C/D snoRNAs and with Rsa1p (29), we tested by electrophoresis mobility shift assays (EMSA) whether the Rsa1p−Hit1p interaction is compatible with binding of Rsa1p to a [C/D snoRNA–Snu13p] complex. As illustrated in Figure 1G, when incubated with a Snu13p–Rsa1p–Hit1p purified ternary complex, a radiolabeled C/D snoRNA is found in a complex displaying a slower mobility compared to the complex formed with the purified Snu13p–Rsa1p heterodimer.…”
Section: Resultsmentioning
confidence: 99%
“…These data are in agreement with previous mapping of the interaction sites at the surface of Snu13p/SNU13 (Supplementary Figure S7) and the recent 3D models of U3 snoRNP (4851) showing that Rrp9p/55.5K and Rsa1p/NUFIP1 interact with independent regions on Snu13p. For example, arginine R 91 of the human SNU13 protein (R 89 for the S. cerevisiae Snu13p) was shown necessary for the recruitment of U3-55K onto the U3 snoRNP (69).…”
Section: Discussionsupporting
confidence: 93%
“…Pih1 interacts directly with Nop58, one of the core protein subunits in box C/D snoRNP (11) and affects its stability (14). Pih1 also interacts with Rsa1, another snoRNP assembly factor through which the R2TP complex may interact with the snoRNP core protein Snu13 (15). Similar to the role of Tah1 in protecting Pih1, a small protein, Hit1, was also identified to interact with and protect Rsa1, thus revealing a complex regulatory network controlling snoRNP assembly in vivo (16).…”
Section: The R2tpmentioning
confidence: 90%